Superheated steam pretreatment of oil palm biomass for improving nanofibrillation of cellulose and performance of polypropylene/cellulose nanofiber composites - Norrrahim, Mohd Nor Faiz (2018)
Cellulose isolation from lignocellulosic materials is a crucial step prior to cellulose nanofiber (CNF) production. Previous studies exhibited that the presence of some amount of hemicellulose would give advantage in the nanofibrillation of cellulose. Superheated steam (SHS) pretreatment has been portrayed as a green approach to partially remove the hemicellulose from lignocellulosic materials. In this research, SHS was used to pretreat three types of oil palm biomass (OPB): oil palm mesocarp fiber (OPMF), oil palm empty fruit bunch (OPEFB) and oil palm frond (OPF). Potassium hydroxide (KOH) pretreatment was used as control experiment. Two processing methods for CNF production were used i.e. wet disk milling (WDM) and electrospinning. CNF obtained was characterised and later, CNF-reinforced polypropylene (PP) biocomposites were prepared using melt-blending method. SHS pretreatment caused partial removal of hemicellulose, producing cellulose with residual hemicellulose of 9 – 14 wt%. This residual hemicellulose assisted in the formation of smaller diameter size CNF from both of the processing methods; compared to the CNF from KOH-pretreated OPB. This can be explained by the role of hemicellulose which facilitated fiber beating and avoided the coalescence of cellulose fibrils. Overall observation showed that WDM managed to produce smaller diameter CNF (20-100 nm) compared to electrospinning (100-150nm). The influence of residual hemicellulose in CNF on PP/CNF biocomposites was evaluated. Several PP:CNF ratio were tested, ranging between 100:0 – 95:5 (wt/wt), with the addition of 3wt% of MA-g-PP as compatibiliser. It was found that 3wt% CNF gave the best improvement in term of mechanical properties, in which tensile and flexural strengths were increased by ~31% and ~28%, respectively, compared to the neat PP. It was interesting to note that PP/SHS-pretreated CNF and PP/KOH-pretreated CNF had almost similar performances; showing that residual hemicellulose left in the CNF did not influence the performance of the PP/CNF biocomposites produced. This finding suggests that complete hemicellulose removal is unnecessary for preparing CNF to be used in biocomposites making; and hence a less harsh pretreatment step is sufficient. In the preparation of nanofiber-plastics compound such as PP/CNF for biocomposites production, the conventional method would involve two separate unit operations for nanofibrillation and melt-compounding, respectively. The ability to combine these two steps in one-pot would add value to the whole process, considering the instability of CNF which is easily agglomerated, and the low productivity due to the downtime in between the two-unit operations. In this research, nanofibrillation of cellulose and melt-compounding of PP and the CNF produced were conducted in an extruder with specially-designed screw for nanofibrillation. Results showed that PP/CNF biocomposites produced through this approach had almost similar performances as PP/CNF biocomposites produced by the conventional method. This finding contributes greatly to PP-based biocomposites processing, since this indicates that the overall biocomposites making could be shortened due to the absence of downtime between the two processes (nanofibrillation and melt-compounding). Overall, the findings from this study are beneficial for cellulose-based nanomaterials research and industries; since the results contributed to an effective, simpler, easier and shorter duration process for CNF and nanofiber-plastics compounding.